The Ethnohistory of the City of Baguio from the pre-colonial to the American colonial period. [article]. - Prill-Brett, June
The City of Baguio will be celebrating its centennial mark on September 1, 2009. In response to this occasion, this paper's purpose i s to look into the ethnohistorical unfolding of events as narrated by informants' memories from ancestors and cross-checked by available historical accounts pertaining ot he creation of the city of Baguio by the American colonial government. It will also discuss the events that led to the creation fo the municipality of Tuba, from the original borderless Ibaloy settlements characterized by the cattle-grazing land called estancias, as well as the socio-political organization of the babaknang/baknang a 'petty plutocracy, which controlled mine tunnels and gold-tradings, and the cattle industry, as well as the guardians and managers of their subordinates-the pastol , abiteg and baga-en. This social class institutionalized the pachit/peshit (lavish feasts of merit) to validate their social rank. The ethonohistory unfolds from the pre-colonial period, through Ibaloy encounters with Spanish punitive expeditions, the insurrectos and the American colonial government. -(from the author)